Editorial: brain‐gut research needs objective measures of disease activity and mental disorders. Issue 10 (26th October 2021) - Mikocka‐Walus, Antonina; Knowles, Simon R.
LINKED CONTENT: This article is linked to Mules et al papers. To view these articles, visit https://doi.org/10.1111/apt.16616 and https://doi.org/10.1111/apt.16649